2020
DOI: 10.2174/1574893614666190919103752
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Epigenetic Signature of Cell Reprogramming by Computational DNA Methylation Profiles

Abstract: Background: DNA methylation plays an important role in reprogramming process. Understanding the underlying molecular mechanism of reprogramming is crucial for answering fundamental questions regarding transition of cell identity. Method: In this study, based on the genome-wide DNA methylation data from different cell lines, the comparative methylation profiles were proposed to identify epigenetic signature of cell reprogramming. Results: The density profile of CpG methylation showed that pluripotent cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In conclusion, we identified incomplete activation of transcription pathways and massive dysregulation of genes related to transcription pathway in NTA embryos. Then, the GRNs indicated that crucial factors responsible for transcription play a coordinated role in epigenome erasure and pluripotency regulation during normal embryo development [ 44 , 45 , 46 , 47 ]. However, in NTA embryos, predicted target genes of transcription pathways were varying in degrees of inhibition and showed a defect in synergy.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we identified incomplete activation of transcription pathways and massive dysregulation of genes related to transcription pathway in NTA embryos. Then, the GRNs indicated that crucial factors responsible for transcription play a coordinated role in epigenome erasure and pluripotency regulation during normal embryo development [ 44 , 45 , 46 , 47 ]. However, in NTA embryos, predicted target genes of transcription pathways were varying in degrees of inhibition and showed a defect in synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the performance, most of the existing predictors are evaluated by cross validation test, which might produce performance bias; we here randomly split the datasets into ( Zuo et al, 2020 ) training set for model training and evaluation and ( Liu et al, 2019 ) independent test set for model robustness validation. Thus, we randomly divided the dataset into training set and testing set with the ratio of 8:2, resulting in 16,000 samples in the training set and 4,000 samples in the testing set.…”
Section: Methodsmentioning
confidence: 99%
“…Epigenetics refers to the reversible and heritable changes in gene function when there is no change in the nuclear DNA sequence ( Zuo et al, 2020 ). Epigenetic phenomena include DNA methylation, RNA interference, histone modification, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its importance, DNA methylation is one of the most widely studied epigenetic modifications (Bergman and Cedar, 2013;Smith and Meissner, 2013). Currently, four out of the DNA modifications, such as N4-methylcytosine (4mC), N6-methyladenine (6mA), 5-methylcytosine (5mC), and 5-hydroxymethylcytosine (5hmC), have been extensively studied (Cheng and Baldi, 2006;Guohua et al, 2017;He et al, 2019;Luo et al, 2020;Zuo et al, 2020c). Schweizer (2008) proposed that 4mC has the effect of protecting the host DNA from degradation by restriction enzymes and belongs to restriction-modification (RM) systems.…”
Section: Introductionmentioning
confidence: 99%